Design of a Ka‐band MW‐level high efficiency gyroklystron for accelerators. Issue 11 (14th June 2018) - Wang, Li; Dong, Kun; He, Wenlong; Wang, Jianxun; Luo, Yong; Cross, Adrian W.; Ronald, Kevin; Phelps, Alan D. R.
Abstract : Design of a three‐cavity Ka‐band MW‐level gyroklystron operating in the TE02 mode in the output cavity while the input cavity and buncher are operating with the TE01 mode is presented. The optimised design of the magnetron injection gun (MIG) and interaction circuit has been completed by particle‐in‐cell simulation and analytically using a MATLAB code. The simulations show the gyroklystron can deliver an output power of more than 1.5 MW with a gain of >35 dB at 36 GHz. The achieved efficiency exceeds 40% when driven by a 95 kV, 45 A beam. The optimised MIG has a transverse velocity spread of <3% when the velocity ratio is around 1.3.